Initiatives collaboratives pour l'enfance Quelles mutations de l'éducation et du travail social ? - Torterat, Frédéric; Azaoui, Brahim (Mutations en éducation et en formation, 2021)
There is a significant body of research nowadays on collaborative research in Social Sciences and Humanities. The present volume documents a range of prospects and analyses related to collaboration in the field of Early Childhood, in France as elsewhere in Europe. It shows to what extent, how and with what objectives such initiatives in education and social work are developped in our contemporary societies.